PENGARUH KOMPETENSI DAN KEPUASAN KERJA TERHADAP KINERJA PERAWAT RUMAH SAKIT SYAFIRA PEKANBARU - Ibnu Mikhail Abdul Muqiit; Machasin '; Restu Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted on SyafiraHospital in Pekanbaru that aims to determine the influences of Competence and Work Statisfaction either simultaneously or partially on Performance of Nurses in Syafira Hospital in Pekanbaru. The methodology in this study is: Competence and job statisfaction significant influence on Nurses performance in Syafira Hospital in Pekanbaru and the dominant factor affecting the performance of Nurses is Job Statisfaction. While the population in this study is the Nurses on Syafira Hospital which amounted to 83 people, with a total sample of 83 respondents. Multiple Linear Regression Analysis method by using SPSS version 21 Simultaneous regression (F test) showed that the independent variables studied (Competence and Job Statisfaction) together (simultaneously) have a significant influence on the dependent variable (Nurse performance). The magnitude of the effect that (R2) by the two independent variables together against the dependent variable, while the remaining is influenced by other variables not examined in this study. The results of the testing that has been done, the partial regression test (t test) showed that each of the independent variables studied (Sress and Job Statisfaction) has a significant effect on Syafira Hospital the dependent variable (Nurse performance). Dominant variables affecting nurse performance in Syafira Hospital in Pekanbaru is Competence where the value of t-counted highest compared with other independent variables.Keywords: Competence, Job Statisfaction and Nurse Performance